ROA on Gold Mines in ZA - Sebehela, Tumellano (Indian Journal of Finance, 2012)
There are virtually no empirical studies in South Africa (ZA) on pricing gold mines using real option analysis (ROA) despite the fact that ZA has relatively good mining prospects across the board and now and then, the mines close and re-open. Therefore, until gold mines in ZA are evaluated using a technique that takes into account the flexibility of mines to close and re-open at later stages, quoted gold mines values are most likely to be subjective. In "extracting" extra value that is normally not captured by traditional valuations methods (TVMs), this empirical study shapes its concepts and principles around Moel and Tufano (2001). Although, Moel and Tufano's (2001) empirical study is North American based, but the real options concepts should be consistent as Moel and Tufano (2001) was based on large data set. Results illustrated that real options concepts have similar impact of South African gold mines as in other countries. Interestingly, interest rates changes have the biggest optionality impact than other real options parameters. In other empirical studies, interest rates changes had optionality impact, but not biggest causal effect.